The Competitiveness of Indonesian Natural Rubber in World Trade on the Agreed Export Tonnage Scheme Policy - Aripranata Aripranata; Supat Isarangkool Na Ayutthaya; Sukanlaya Choenkwan (Program Studi Agribisnis, Fakultas Pertanian, Universitas Udayana Jalan PB.Sudirman Denpasar, Bali, Indonesia. Telp: (0361) 223544 Email: soca@unud.ac.id, 2024)
The agricultural sector, particularly natural rubber commodities, isexperiencing rapid development, especially in Indonesia, the biggestproducing nation for rubber worldwide. A product is consideredcompetitive if it can compete effectively in the market. Highcompetitiveness in a product is reflected in its good price andquality. However, if a product cannot compete, it will lead to newproblems. Therefore, various analyses, such as the competitivenessanalysis of Indonesian natural rubber, are necessary. This researchaims to analyze the competitiveness of Indonesian natural rubberand explain the factors influencing this competitiveness. Annualdata from 2000 to 2002 was collected from the Food and AgricultureOrganization of the United Nations, the World Bank, the World TradeOrganization, the Ministry of Agriculture of the Republic ofIndonesia, and the Ministry of Trade of the Republic of Indonesia. Aquantitative approach using the Ordinary Least Squares (OLS)method is employed. The research is conducted in Indonesia due toits status as one of the countries with the highest natural rubberproduction value globally. The analysis tools used include MicrosoftExcel and SPSS 28.0.1.0. The results of the competitiveness analysisindicate that Indonesian natural rubber farming has a competitiveadvantage in world trade. Of the four factors affectingcompetitiveness, only Indonesia's natural rubber production showssignificance, while the exchange rate, export value, and policies donot have a significant impact